Governance and its Impact on Quality Performance in Iraqi Faculties of Physical Education and Sports Sciences Governance and its Impact on Quality Performance - Flayyih, Bahaa Hayder (International Journal of Psychosocial Rehabilitation, 2020)
The research problem is reflected in the following questions: Is there a correlation between governance and quality of performance in the faculties of physical education and sports sciences (FPESS)1? Is there an impact on performance quality in the FPESS? The objectives of the research are to identify the relationship and impact between the two variables of the research. The researchers used the descriptive method in the analytical method of its suitability and the nature of the research problem included the research sample on (200) lecturers in some (FPESS) and the exploratory experiment sample was (15) and the sample numbers was (60) and sample application (125) The researchers numbered a scale that includes two tools, the first to measure governance, and the second to measure the performance quality, as the researchers followed the following procedures: making a survey of the scale addressed to a number of lecturers in the (FPESS).The scale, which includes two tools, the first includes (25) paragraphs to measure areas (transparency, accountability, justice and equality, rule of law, participation) The performance quality measure included (25) and areas (creativity, job satisfaction, user satisfaction, turnover, organizational commitment) and the researchers concluded that the moderate compatibility between the opinions of the research sample on after creativity, indicates the existence of support but limited for new innovations and ideas by (FPESS), He recommended that (FPESS) should invest in the nature of the positive relationship between the variables of research governance and quality of performance, in improving the administrative reality of them.